LEGAL PROTECTION OF ONLINE BUSINESS TRANSACTION (E-COMMERCE) DURING THE COVID-19 PANDEMIC IN INDONESIA - Matompo, Osgar Sahim (Legal Standing : Jurnal Ilmu Hukum, 2020)
In Indonesia, the electronic business (e-commerce) transaction has shown a rapid development after the application of the social distancing in the efforts to handle the spread of the coronavirus disease (Covid-19). Initially, the increase of the people?s interests to shop online was to buy masks and hand sanitizers for protection against the disease. Then, there was an increase of interest to buy stationery (as there is the trend of working and studying from home) and also medical equipment. Yet, in its application, there are many cases of where the customers experienced loss due to the use of this type of business transaction. There are legal protections on electronic transaction which have been violated during the time of the Covid-19 pandemic. These transactions are regulated on the Constitution No. 11 of 2007 regarding Information and Electronic Transaction and also Article 1365 of Burgerlijke Wetboek (BW). The stipulations of the BW Article 1365 may be applied in cases which violate the law in online business transactions (e-commerce). To fill in the legal void, there needs to be an extensive legal interpretation.